Shallot growth and yield supported by irrigation and nitrogen application in utilizing dry land area in Mesuji, Lampung Province, Indonesia - Manik, Tumiar Katarina; Timotiwu, Paul B.; Mua’ddin, Mua’ddin (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Lampung Province, Indonesia local government intended to extend shallot cultivation in Mesuji Regency, Lampung (-3.86, 105.43). Mesuji has 21,863.5 ha dry land area, with unproductive land of 10,325.6 ha which could be potential for growing shallot. However, horticulture crops such as shallot often face obstacles in dry land since dry land characterized with poor soil nutrient and limited water. The objective of this research are to analyze the effects of nitrogen fertilizer and different irrigation volumes on shallot growth and production, investigate shallot suitability to Mesuji agro-climate, and estimate shallot yield potential in Mesuji. The treatments on factorial split block were: without N, 80 kg N ha-1 , 160 kg N ha-1, and 240 kg N ha-1 and the irrigation levels: 25, 50, 75 and 100% of ETc; ETc is crops evapotranspiration. The Mesuji agro-climate was evaluated using standardized precipitation index (SPI) and the yield was simulated by Aquacrop model. The results showed that the effort of shallots production with a high fresh weight of bulbs and biomass in the Mesuji area requested water at least 75% ETc and N fertilizer doses of 160 kg N ha-1. The SPI indicated near normal condition was more than 65%, and drought existed in a small percentage in both places (a total of 16.9%  for Brebes the centre of shallot production  and 19.43% for Mesuji). The AquaCrop simulation gave a good yield estimation (simulated 19.451 ton ha-1 and observed 17.351 ton ha-1). There is a possibility that shallot will grow well in the Mesuji area even though the quality of the shallot should be further tested.